Assessing The Challenges of Executing State Sponsored Projects in Ghana: A Case of Getfund Construction Projects in The Upper West Region - Iddrisu, Abdul Ganiyu (South Asian Journal of Social Sciences and Humanities, 2022)
The core mandate of GETFund is to provide funding to supplement government budgetary allocations in the provision of educational infrastructure at all levels of education from pre-tertiary to tertiary level as stipulated in the (GETFund Act, 2000 Act 581). The study aims to evaluate the challenges and managerial skills adopted by GETFund contractors. The study’s objective is to examine the challenges of GETFund construction projects, identify factors affecting GETFund projects and devise effective strategies to enhance effective GETFund project execution in the Region. The study adopted a descriptive survey design. Sixty-five clients, twenty-one consultants, and sixty-two contractors totaling one hundred and forty-eight were sampled for the study. Questionnaires, interviews, and observation were the main methods adopted for data collection. The data were analyzed using descriptive statistics. The study revealed that the most leading challenges affecting the efficient execution of GETFund construction projects are political and financial. Furthermore, the most leading factors confronting efficient GETFund construction projects execution in the Region are cost and time. In addition, the study revealed that most of the contractors’ agents executing GETFund projects do not have the requisite technical personnel, expertise, and resources, making it difficult to understand/interpret drawings and other specifications given to them by project consultants. The study recommended that professional regulatory bodies such as Building and Road Research Institute (BRRI) organize in-service training to improve the management skills of companies.